Does Pollution Drive Achievement? The Effect of Traffic Pollution on Academic Performance - Jennifer Heissel; Claudia Persico; David Simon (Institute of Labor Economics (IZA), 2019)
We examine the effect of school traffic pollution on student outcomes by leveraging variation in wind patterns for schools the same distance from major highways. We compare within-student achievement for students transitioning between schools near highways, where one school has had greater levels of pollution because it is downwind of a highway. Students who move from an elementary/middle school that feeds into a "downwind" middle/high school in the same zip code experience decreases in test scores, more behavioral incidents, and more absences, relative to when they transition to an upwind school. Even within zip codes, microclimates can contribute to inequality.
Keywords: Q53; I24; I14; 330; air pollution; academic achievement; child health